End-stage renal disease after occupational lead exposure: 20 years of follow-up. Issue 6 (14th December 2016) - Evans, Marie; Discacciati, Andrea; Quershi, Abdul Rashid; Åkesson, Agneta; Elinder, Carl-Gustaf
Abstract : Objectives: Whether low-level exposure to lead may give rise to chronic kidney disease or end-stage renal disease (ESRD) is debated. In this study, we aimed to specifically investigate if low-level occupational exposure to lead was associated with increased incidence of ESRD. Methods: The incidence of starting renal replacement therapy as a result of ESRD was examined in a cohort of10 303 lead-workers who had controlled blood lead concentrations due to a compulsory occupational health surveillance programme in Sweden during the time period 1977–1990. The ESRD incidence (obtained through register-linkage) among the lead-exposed workers was compared with the age, sex and calendar period-adjusted expected incidence based on data from the Swedish renal registry. Dose–response association was evaluated in external (general population) and internal (within the occupational cohort) comparisons by highest achieved blood lead level. Results: There were 30 (0.29%) individuals in the cohort who developed ESRD during the median follow-up period of 26.3 years. The standardised incidence ratio (SIR) for ESRD incidence was 0.79 (95% CI 0.54 to 1.13). Among those who achieved the highest blood lead (>41.4 µg/dL), the SIR was 1.01 (0.44 to 1.99). There was no evidence of a dose–response relationship between the maximum achieved blood lead or the cumulative blood lead exposure and ESRD in external or internal comparisons. Conclusions: This study of workers with documented occupational lead exposures followed for 20 years shows no statistically significant association between lead exposure (following the current occupational recommendations for Sweden) and ESRD.